Food production and density: the design of a high-rise housing development in Singapore - Bay, Joo; Wee, O. (Earthscan from Routledge, 2017)
The issue of food security is shifting from the periphery of the urban design/architectural discourse into the centre. The growing impetuous to recognize the disproportional rate at which population groeth is occurring (both globally and in urban areas) and rate of food production remaining stable has entered the realm of urban design and architecture. Cities such as Singapore reveal an almost non-existent arable land supply, and are, consequently, heavily dependent on food imports. Singapore’s continued rapid urbanization has resulted in an increasingly dense city; however, a response to the correlation between density and food security is unresolved. How can such cities address the oxymoronic challenge presented – to secure sustainable future food supply whilst maintaining urbanization? Can the paradoxical spatial qualities of agricultural food production and the density of housing coalesce t produce a new architectural typology of food security and urban housing? Surbana Jurong Consultants of Singapore’s theoretical framework for the R4 Apartments and Food Production Tower projects seels to explore this paradigm. Here the R4 Apartments attempt to integrate multi-tiered small-scale food production into apartment living technologies and the Food Tower attempts to envisage a seminal large-scale response to food production only. Whilst this is not the conclusive solution to the rojected 2050 food security crisis, this can contribute to the greater collective solution required to address similar problems in the discourse of stainable food security occurring within the density of urbanity.